Colored radiation refrigeration coating as well as preparation method and application thereof

By using the self-assembly and pulverization technology of sulfonated cellulose nanocrystals, a colored radiation cooling coating was prepared, which solved the brittleness problem and realized a low-cost, large-area colored radiation cooling coating that maintains high reflectivity and emissivity and reduces building energy consumption.

CN121108869APending Publication Date: 2025-12-12INNOVATION CENTER OF YANGTZE RIVER DELTA ZHEJIANG UNIVERSITY

Patent Information

Application Number
CN202511335669.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-18
Publication Date
2025-12-12

AI Technical Summary

Technical Problem

Existing colored radiative cooling materials suffer from brittleness, making them difficult to apply on a large scale and costly, thus failing to simultaneously meet the requirements of aesthetics and efficient cooling.

Method used

A colored film was formed by the self-assembly of sulfonated cellulose nanocrystals. After heat treatment and pulverization, the film was mixed with resin to form structural color microparticles, which were then coated onto a high-reflectivity layer to prepare a colored radiation-cooling coating.

Benefits of technology

A low-cost, large-area application of colored radiative cooling coating has been achieved, which maintains high solar reflectivity and emissivity, reduces building cooling energy consumption in summer, and has a colored appearance and radiative cooling effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121108869A_ABST
    Figure CN121108869A_ABST
Patent Text Reader

Abstract

The invention provides a colored radiation refrigeration coating as well as a preparation method and application thereof, and belongs to the technical field of building materials. The preparation method comprises the following steps: carrying out self-assembly on a sulfonated cellulose nanocrystal aqueous solution to obtain a colored film; sequentially carrying out heat treatment and crushing on the colored film to obtain structural color particles; mixing the structural color particles with resin to obtain a mixture; and coating a reflecting layer with the mixture to obtain the colored radiation refrigeration coating. According to the colored radiation refrigeration coating and the preparation method thereof, the sulfonated cellulose nanocrystals form an expandable colored coating in a manner of crushing and mixing with resin, so that the problem of brittleness of the cellulose nanocrystals in use is solved, and the obtained colored radiation refrigeration coating can reduce the refrigeration energy consumption in a building use process in summer. The reflectivity of the prepared colored radiation refrigeration coating is 90-93%, the emissivity of the prepared colored radiation refrigeration coating is 87-92%, and a radiation refrigeration effect can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of building materials, in particular to a color radiation refrigeration coating and a preparation method and application thereof. BACKGROUND

[0002] The building industry is an important field of energy consumption and carbon emission. In order to maintain the stability of the indoor thermal and humid environment of the building, the use of air conditioners brings huge power consumption. Radiation refrigeration materials are materials that use thermal radiation to dissipate heat to the cold outer space. Radiation refrigeration materials can efficiently reflect the thermal radiation of sunlight in the 0.3~2.5μm band, generally requiring a solar reflectance of more than 90%; and can efficiently emit thermal radiation in the "atmospheric window" band (8~13μm), generally requiring an emissivity of more than 90%, so that heat can pass through the atmosphere into space, thereby achieving a cooling effect below the ambient temperature without any external energy input, and is considered as a sustainable development technology. Therefore, it can be used for building external interfaces such as building external walls and roofs, and is expected to become a substitute technology for traditional high-energy-consumption refrigeration equipment (such as air conditioners).

[0003] For traditional materials with high solar reflectance, since it is necessary to efficiently reflect light of various wavelengths, they often have a pure white appearance and cannot fully meet the aesthetic requirements of the building external surface. Therefore, colored radiation refrigeration devices have become the research direction of building energy-saving materials. Such devices are often composed of a bottom solar reflectance layer and a top color layer. The colors in nature can be divided into pigment colors and structural colors. Pigment color is a color caused by specific chemicals (pigments), which is often based on the absorption of specific wavelengths in the visible light range, which will reduce the reflectivity of the material to sunlight. Structural color, also known as physical color, is an optical phenomenon that depends on the interaction between the microstructure of a substance and light waves. The process of structural color presentation does not involve absorption of color, so it can present color while not reducing the reflectivity of the material. Currently, structural color is mostly prepared by metal-insulator-metal, multilayer dielectric structure, periodic structure, and plasmonic nanoparticles. However, the above preparation methods are relatively expensive and difficult to prepare on a large scale. Cholesteric liquid crystal structures prepared from cellulose nanocrystals can achieve structural color at a lower cost, but the formed film is brittle and has problems in large-area use. SUMMARY

[0004] Therefore, the purpose of the present application is to provide a color radiation refrigeration coating and a preparation method and application thereof. The preparation method of the present application forms an expandable color coating, solving the problem of brittleness of cellulose nanocrystals in use.

[0005] In order to achieve the above-mentioned purpose of the application, the present application provides the following technical solutions: The application provides a preparation method of a color radiation refrigeration coating, comprising the following steps: The sulfonated cellulose nanocrystal aqueous solution is self-assembled under solvent-removing conditions to obtain a color film; The color film is sequentially subjected to heat treatment and crushing to obtain structural color microparticles; The structural color microparticles are mixed with a resin to obtain a mixture; The mixture is coated on a reflective layer to obtain the color radiation refrigeration coating.

[0006] Preferably, the sulfonated cellulose nanocrystals in the sulfonated cellulose nanocrystal aqueous solution have a diameter of 3-7 nm and a length of 100-300 nm.

[0007] Preferably, the mass fraction of the sulfonated cellulose nanocrystals in the sulfonated cellulose nanocrystal aqueous solution is 4%-10%.

[0008] Preferably, an inorganic chloride salt is further added during the self-assembly.

[0009] Preferably, the inorganic chloride salt comprises one or more of sodium chloride, potassium chloride and zinc chloride.

[0010] Preferably, during the self-assembly, the concentration of the inorganic chloride salt in the reaction system is 0-2 mmol / L and is not 0.

[0011] Preferably, the heat treatment is performed at a temperature of 150-180 DEG C for 30-60 min.

[0012] Preferably, the mass ratio of the structural color microparticles to the resin is 10-20:100.

[0013] The application further provides the color radiation refrigeration coating prepared by the preparation method, comprising a reflective layer and a structural color layer, and the reflectivity of the color radiation refrigeration coating is 90-93% and the emissivity is 87-92%.

[0014] The application further provides the application of the color radiation refrigeration coating in the field of building materials.

[0015] The application provides a preparation method of a color radiation refrigeration coating, comprising the following steps: the sulfonated cellulose nanocrystal aqueous solution is self-assembled under solvent-removing conditions to obtain a color film; the color film is sequentially subjected to heat treatment and crushing to obtain structural color microparticles; the structural color microparticles are mixed with a resin to obtain a mixture; and the mixture is coated on a reflective layer to obtain the color radiation refrigeration coating.

[0016] Compared with the prior art, the application has the following beneficial effects: The present application solves the brittleness problem of cellulose nanocrystals in use by forming an expandable color coating through crushing and mixing with resin, and the obtained color radiation refrigeration coating can reduce the refrigeration energy consumption during the use of buildings in summer.

[0017] The present application also provides a color radiation refrigeration coating prepared by the preparation method, which has a reflective layer with high solar reflectance as a bottom layer and a structural color layer with high emissivity as a top layer. The structural color layer formed by the mixture prepared by the present application has an absorption rate of less than 1% to solar light, so that after being coated on a high reflective layer material (reflectivity greater than 95%), the solar reflectance of the composite material is only reduced by 2-3% compared with the high reflective layer material, reaching 91-93%, and the color radiation refrigeration coating has a colorful appearance. The color radiation refrigeration coating inherits the high emissivity of sulfonated cellulose nanocrystals, and the emissivity reaches 87-92%, so that the color radiation refrigeration coating can achieve the effect of radiation refrigeration. BRIEF DESCRIPTION OF DRAWINGS

[0018] Figure 1 It is a transmission electron microscope picture of sulfonated cellulose nanocrystals; Figure 2 It is a macroscopic picture of the color film obtained in Examples 1, 5 and 9; Figure 3 It is a microscopic picture of the color film obtained in Examples 1, 5 and 9; Figure 4 It is a picture of the structural color microparticle under a microscope in Example 1; Figure 5 It is a solar reflectance spectrum diagram of the color radiation refrigeration coating in Example 1; Figure 6 It is a solar reflectance spectrum diagram of the color radiation refrigeration coating in Example 2; Figure 7 It is a solar reflectance spectrum diagram of the color radiation refrigeration coating in Example 3; Figure 8 It is a solar reflectance spectrum diagram of the composite film in Comparative Example 1; Figure 9 It is a solar reflectance spectrum diagram of the composite film in Comparative Example 2; Figure 10 It is a solar reflectance spectrum diagram of the composite film in Comparative Example 3. DETAILED DESCRIPTION

[0019] The present application provides a preparation method of a color radiation refrigeration coating, which comprises the following steps: Self-assemble the sulfonated cellulose nanocrystal aqueous solution under the condition of removing the solvent to obtain a color film; Heat treat and crush the color film in sequence to obtain structural color microparticles; mixing the structural color microparticles with a resin to obtain a mixture; coating the mixture on a reflective layer to obtain the color radiation refrigeration coating.

[0020] In the present application, the raw materials used are commercially available unless otherwise specified.

[0021] The present application performs self-assembly of the sulfonated cellulose nanocrystal aqueous solution under solvent-free conditions to obtain a color film.

[0022] In the present application, the diameter of the sulfonated cellulose nanocrystals in the sulfonated cellulose nanocrystal aqueous solution is preferably 3-7 nm, and can be 3, 4, 5, 6, or 7 nm, and the length is preferably 100-300 nm, and can be 100, 150, 200, 250, or 300 nm, and the size of the sulfonated cellulose nanocrystals can form structural color.

[0023] In the present application, the sulfonated cellulose nanocrystals are preferably obtained by obtaining cellulose from wood and then hydrolyzing the cellulose with sulfuric acid.

[0024] In the present application, the mass fraction of the sulfonated cellulose nanocrystals in the sulfonated cellulose nanocrystal aqueous solution is preferably 4%-10%, and can be 4%, 5%, 6%, 7%, 8%, 9%, or 10%.

[0025] In the present application, an inorganic chloride salt is preferably added during the self-assembly, and the inorganic chloride salt functions to adjust the color.

[0026] In the present application, the inorganic chloride salt preferably includes one or more of sodium chloride, potassium chloride, and zinc chloride.

[0027] In the present application, the concentration of the inorganic chloride salt in the reaction system during the self-assembly is preferably 0-2 mmol / L, and is not 0, and can be 1 or 2 mmol / L, and the greater the concentration of the inorganic chloride salt, the more the structural color will move towards blue, and more than 2 mmol / L will be colorless.

[0028] The present application preferably adds the inorganic chloride salt to the sulfonated cellulose nanocrystal aqueous solution to perform the self-assembly.

[0029] In the present application, the temperature of the self-assembly is preferably room temperature, and the time is preferably 24-48 h, and can be 24, 36, or 48 h, and during the self-assembly, the reaction system is evaporated at room temperature, the sulfonated cellulose nanocrystals are self-assembled, an internal cholesteric phase periodic structure is formed, and a color film is presented on the surface.

[0030] The reaction system is preferably poured into a plastic culture dish for the self-assembly.

[0031] In the present application, the thickness of the color film is preferably 60±2 μm.

[0032] After obtaining the color film, the color film is sequentially subjected to heat treatment and crushing to obtain structural color microparticles.

[0033] In the present application, the temperature of the heat treatment is preferably 150-180℃, and can be 150, 160, 170 or 180℃, and the time is preferably 30-60 min, and can be 30, 40, 50 or 60 min. During the heat treatment, the color film is further dehydrated. Since the sulfonated cellulose nanocrystals have low thermal stability, the sulfonic acid groups are separated from the cellulose nanocrystals at high temperatures, thereby strengthening the hydrogen bonding force between the cellulose nanocrystals and making the color film hydrophobic.

[0034] In the present application, the crushing is preferably grinding, and after the grinding is completed, the grinding is preferably sieved with a screen to obtain structural color microparticles with three particle sizes of greater than 150 μm, 75-150 μm and less than 75 μm, respectively.

[0035] After obtaining the structural color microparticles, the structural color microparticles are mixed with a resin to obtain a mixture.

[0036] In the present application, the mass ratio of the structural color microparticles to the resin is preferably 10-20:100, and can be 10:100, 15:100 or 20:100.

[0037] In the present application, the resin preferably includes an epoxy resin and / or a silicone resin, and more preferably is SJ-2200K silicone modified resin.

[0038] In the present application, the mixing is preferably stirring at a speed of 800-1500 rpm (and can be 800, 1000, 1200 or 1500 rpm) for 10-20 min to ensure that the structural color microparticles and the resin are fully mixed.

[0039] The present application forms an expandable color coating by crushing and mixing with a resin, thereby solving the problem of brittleness of cellulose nanocrystals in use.

[0040] After obtaining the mixture, the mixture is coated on a reflective layer to obtain the color radiative cooling coating.

[0041] In the present application, the reflectivity of the reflective layer is preferably not less than 95%.

[0042] In the present application, the reflective layer preferably comprises an aluminum foil, a silver foil or an aerogel film, and the aerogel film is preferably a composite cellulose aerogel disclosed in Chinese Patent CN202510517705.9.

[0043] In the present application, the thickness of the coating is preferably 60-120 μm, and can be 60, 70, 80, 90, 100, 110 or 120 μm.

[0044] In the present application, the coating is preferably spin coating.

[0045] The present application also provides a color radiation refrigeration coating prepared by the preparation method described in the above technical solution, comprising a reflective layer and a structural color layer, and the color radiation refrigeration coating has a reflectivity of 90-93% and an emissivity of 87-92%, and has a color appearance at the same time.

[0046] Compared with other color radiation refrigeration devices, the color radiation refrigeration coating provided by the present application has a high solar reflectivity and emissivity, and has a low preparation cost and a simple preparation method. The reasons are as follows: 1. High solar reflectivity and emissivity. The generation of color can be divided into chemical color and physical color. The chemical color generates color mainly depending on the different absorption degrees of different wavelengths of light, while the physical color, also known as structural color, generates color by physical phenomena such as refraction, interference and diffraction of wavelengths, and thus has a very low light absorption rate. The sulfonated cellulose nanocrystal will form a structural color in the evaporation-driven self-assembly process, and will not reduce the solar reflectivity when being combined with a high reflective layer.

[0047] 2. Preparation cost. The sulfonated cellulose nanocrystal is obtained by obtaining cellulose from wood and then hydrolyzing the cellulose by sulfuric acid, and the raw material source is extensive and the preparation method is relatively simple. The process cost from the sulfonated cellulose nanocrystal aqueous solution to the color film is relatively low. Compared with other methods for preparing structural color materials such as structural color materials based on photonic crystals (for example, structural color materials based on multilayer film interference) and structural color materials based on periodic materials, the cost of the structural color materials based on periodic materials is relatively low.

[0048] 3. The color radiation refrigeration coating has scalability. The brittle color film prepared is crushed to obtain micron-level structural color particles, which are then mixed with a resin and finally coated on a material having high reflectivity, and the coating area can be controlled, so that large-area preparation can be achieved.

[0049] The present application also provides an application of the color radiation refrigeration coating described in the above technical solution in the field of building materials.

[0050] The present application does not have special limitations on the specific mode of the application, and any mode well known to those skilled in the art can be used.

[0051] The technical solutions in the present application will be described clearly and completely below in combination with the embodiments in the present application. Obviously, the described embodiments are only some of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all the other embodiments obtained by a person of ordinary skill in the art without creative effort belong to the scope of protection of the present application.

[0052] The sulfonated cellulose nanocrystal used in the embodiments and comparative examples has a diameter of 3 nm and a length of 100 nm, Figure 1 The transmission electron microscope picture of the sulfonated cellulose nanocrystal is shown in Figure 1. The resin is SJ-2200K organic silicon modified resin.

[0053] Embodiment 1 A 4wt% sulfonated cellulose nanocrystal aqueous solution was taken and poured into a plastic culture dish. The cellulose nanocrystal aqueous solution was allowed to evaporate at room temperature. After the solvent was completely evaporated, a colored film was obtained. The colored film was placed in an oven at 180℃ for 30 min for heat treatment. The heat-treated cellulose nanocrystal colored film was ground and sieved with a screen to obtain structural color microparticles with a size of less than 75 μm. The microparticles were mixed with a resin, and the mass ratio of the microparticles to the resin was 10:100. The mixture was stirred at a speed of 1200 rpm for 10 min. The obtained mixture was coated on a reflective layer with high solar reflectance (reflectivity of 95%, silver foil) to obtain a colored radiation refrigeration coating, and the coating thickness was 60 μm.

[0054] Embodiment 2 The method was operated according to Embodiment 1, except that the colored film was ground to obtain structural color microparticles with a size of 75-150 μm.

[0055] Embodiment 3 The method was operated according to Embodiment 1, except that the colored film was ground to obtain structural color microparticles with a size of more than 150 μm.

[0056] Embodiment 4 The method was operated according to Embodiment 1, except that the obtained mixture was coated on a cellulose aerogel layer to obtain a colored radiation refrigeration coating. The cellulose aerogel layer was a composite cellulose aerogel prepared according to the method of Embodiment 1 of Chinese patent CN202510517705.9.

[0057] Embodiment 5 A 4wt% sulfonated cellulose nanocrystal aqueous solution was taken, and sodium chloride was added to make the concentration of sodium chloride in the self-assembly reaction system 1 mmol / L. The solution was poured into a plastic culture dish, and the cellulose nanocrystal aqueous solution was allowed to evaporate at room temperature. After the solvent was completely evaporated, a colored film was obtained. The colored film was placed in an oven at 180°C for 30 min for heat treatment. The cellulose nanocrystal colored film after heat treatment was ground, and then sieved with a screen to obtain structural color microparticles with a size of less than 75 μm. The microparticles were mixed with resin, and the mass ratio of the microparticles to the resin was 10:100. The mixture was stirred at a speed of 1200 rpm for 10 min. The obtained mixture was coated on a reflective layer with high solar reflectance (reflectivity 95%, silver foil) to obtain a colored radiation refrigeration coating, and the coating thickness was 60 μm.

[0058] Example 6 The method of Example 5 was operated, except that the colored film was ground to obtain structural color microparticles with a size of 75-150 μm.

[0059] Example 7 The method of Example 5 was operated, except that the colored film was ground to obtain structural color microparticles with a size of more than 150 μm.

[0060] Example 8 The method of Example 5 was operated, except that the obtained mixture was coated on a cellulose aerogel layer to obtain a colored radiation refrigeration coating. The cellulose aerogel layer was a composite cellulose aerogel prepared by the method of Example 1 of Chinese patent CN202510517705.9.

[0061] Example 9 The method of Example 5 was operated, except that the concentration of sodium chloride in the self-assembly reaction system was 2 mmol / L.

[0062] Example 10 The method of Example 9 was operated, except that the colored film was ground to obtain structural color microparticles with a size of 75-150 μm.

[0063] Example 11 The method of Example 9 was operated, except that the colored film was ground to obtain structural color microparticles with a size of more than 150 μm.

[0064] Example 12 The procedure of Example 9 was followed, except that the resulting mixture was coated on a cellulose aerogel layer to obtain a color radiative cooling coating. The cellulose aerogel layer was a composite cellulose aerogel prepared according to the procedure of Example 1 of Chinese patent CN202510517705.9.

[0065] Comparative Example 1 A commercially available red transparent PET film was used, and after being attached with a reflective film (reflectivity 95%, silver foil), a composite film with a red appearance was obtained.

[0066] Comparative Example 2 A commercially available green transparent PET film was used, and after being attached with a reflective film (reflectivity 95%, silver foil), a composite film with a green appearance was obtained.

[0067] Comparative Example 3 A commercially available blue transparent PET film was used, and after being attached with a reflective film (reflectivity 95%, silver foil), a composite film with a blue appearance was obtained.

[0068] Table 1 shows the reflection wavelength, solar reflectance, and emissivity data of the examples and comparative examples. It can be seen that the solar reflectance of Examples 1-12 is significantly higher than that of Comparative Examples 1-3, indicating that the structural color formed by using sulfonated cellulose nanocrystals is more conducive to maintaining the high reflectivity of the reflective layer than the color formed by pigments, and is conducive to the realization of radiative cooling performance.

[0069] Table 1 shows the reflection wavelength, solar reflectance, and emissivity data of the examples and comparative examples. It can be seen that the solar reflectance of Examples 1-12 is significantly higher than that of Comparative Examples 1-3, indicating that the structural color formed by using sulfonated cellulose nanocrystals is more conducive to maintaining the high reflectivity of the reflective layer than the color formed by pigments, and is conducive to the realization of radiative cooling performance.

[0070] Figure 2 The macroscopic pictures of the color films obtained in Examples 1, 5, and 9 are shown in FIG. 1, and the scale in the figure is 2 cm. It can be seen that by adjusting the concentration of sodium chloride (0, 1, and 2 mmol / L, respectively), color films of different colors can be obtained. Figure 3 The microscopic pictures of the color films obtained in Examples 1, 5, and 9 are shown in FIG. 2, and the scale in the figure is 250 μm. It is proved that the color films can exhibit the corresponding color seen by the human eye at the microscopic scale, and the color films are the basis for subsequent grinding and preparation of structural color microparticles.

[0071] Figure 4 The picture of the structural color microparticles under a microscope in Example 1 is shown in FIG. 3.

[0072] Figure 5 The solar reflectance spectrum of the color radiative cooling coating in Example 1 is shown in FIG. 4, Figure 6 The solar reflectance spectrum of the color radiative cooling coating in Example 2 is shown in FIG. 5, Figure 7The solar reflectance spectrum of the color radiation cooling coating in Example 3, Figures 5-7 The reflectance spectra of the sun in the range of 250~2500nm, the radiation cooling material needs to have high reflectivity in the solar spectrum range, and high emissivity in the long-wave range, it can be seen that the color radiation cooling device formed by using the sulfonated cellulose nanocrystal structural color has high reflectivity.

[0073] Figure 8 The solar reflectance spectrum of the composite film in Comparative Example 1, Figure 9 The solar reflectance spectrum of the composite film in Comparative Example 2, Figure 10 The solar reflectance spectrum of the composite film in Comparative Example 3, Figures 8-10 The reflectance spectra of the sun in the range of 250~2500nm, the radiation cooling material needs to have high reflectivity in the solar spectrum range, and high emissivity in the long-wave range, in order to form color, the color based on absorption will form an absorption peak in the visible light band in the solar light, in Comparative Examples 1~3, an absorption peak is formed in the range of 500~1000nm due to absorption of specific wavelengths, resulting in a decrease in reflectivity, which cannot meet the requirement of high reflectivity.

[0074] The above only describes the preferred embodiments of the present application, and does not limit the present application in any form. It should be noted that for ordinary skilled persons in the art, without departing from the principles of the present application, a number of improvements and refinements can be made, and these improvements and refinements should also be considered as the protection scope of the present application.

Claims

1. A method of making a colored radiative cooling coating, characterized in that, The method comprises the following steps: Self-assembling sulfonated cellulose nanocrystals in an aqueous solution under solvent-removing conditions to obtain a colored film; Heat treating and crushing the colored film in sequence to obtain structural color microparticles; Mixing the structural color microparticles with a resin to obtain a mixture; Coating the mixture on a reflective layer to obtain the colored radiation refrigeration coating.

2. The production method according to claim 1, characterized by, The sulfonated cellulose nanocrystals in the aqueous solution have a diameter of 3-7 nm and a length of 100-300 nm.

3. The production method according to claim 1 or 2, characterized by, The mass fraction of the sulfonated cellulose nanocrystals in the aqueous solution is 4-10%.

4. The production method according to claim 1 or 2, characterized by, An inorganic chloride salt is added during the self-assembling.

5. The preparation method according to claim 4, characterized in that, The inorganic chloride salt comprises one or more of sodium chloride, potassium chloride and zinc chloride.

6. The preparation method according to claim 4, characterized in that, During the self-assembling, the concentration of the inorganic chloride salt in the reaction system is 0-2 mmol / L and is not 0.

7. The preparation method according to claim 1, characterized in that, The heat treatment is performed at a temperature of 150-180 ℃ for 30-60 min.

8. The method of claim 1, wherein, The mass ratio of the structural color microparticles to the resin is 10-20:

100.

9. The colored radiative cooling coating produced by the method of any one of claims 1-8, wherein, The colored radiation refrigeration coating comprises a reflective layer and a structural color layer, has a reflectivity of 90-93% and an emissivity of 87-92%.

10. Application of the colored radiation refrigeration coating of claim 9 in the field of building materials.

Citation Information

Patent Citations

  • Composite cellulose aerogel as well as preparation method and application thereof

    CN120098319A

Cited By

  • Hydrochromic self-adaptive color radiation refrigeration coating and application thereof

    CN122255799A